The mGluR5 antagonist AFQ056 does not affect methylation and transcription of the mutant FMR1 gene in vitro - Tabolacci Elisabetta; Pirozzi Filomena; Gomez-Mancilla Baltazar; Gasparini Fabrizio; Neri Giovanni (BMC, 2012)
Abstract Background Fragile X syndrome (FXS), the leading cause of inherited mental retardation, is due to expansion and methylation of a CGG sequence in the FMR1 gene, which result in its silencing and consequent absence of FMRP protein. This absence causes loss of repression of metabotropic glutamate receptor 5 (mGluR5)-mediated pathways resulting in the behavioral and cognitive impairments associated with FXS. In a randomized, double-blind trial it was recently demonstrated a beneficial effect of AFQ056, a selective inhibitor of metabotrobic glutamate receptor type 5 (mGluR5), on fully methylated FXS patients respect to partially methylated FXS ones. Methods To determine whether AFQ056 may have secondary effects on the methylation and transcription of FMR1, here we treated three FXS lymphoblastoid cell lines and one normal control male line. A quantitative RT-PCR was performed to assess transcriptional reactivation of the FMR1 gene. To assess the methylation status of the FMR1 gene promoter it was carried out a bisulphite sequencing analysis. Results Both FMR1-mRNA levels and DNA methylation were unmodified with respect to untreated controls. Conclusions These results demonstrate that the AFQ056 effect on fully methylated FXS patients is not due to a secondary effect on DNA methylation and consequent transcriptional activation of FMR1.